Linguistic insecurity and phonetic change in northwest Catalan - Carrera-Sabaté, Josefina (Sociolinguistic Studies, 2005)
The purpose of this paper is to explain an ongoing linguistic change in North - Eastern Catalan by means of an analysis of speakers’ subjectivity and, more specifically, through the notion of linguistic insecurity. The process of phonic change analysed is the variation of pre-stressed vowels in utterance-initial position in words such as enciam ‘lettuce’, escola ‘school’ and edifici‘ building’. The realisation of these vowels has traditionally been [a]. However, at present there is a tendency to adapt their pronunciation to their corresponding written forms, that is to say, [e]. Speakers’ responses to which pre-stressed vowels they consider to be the best representatives and which ones they believe to be using have enabled us to establish the highest rate of linguistic insecurity in those speakers who are at an intermediate stage of this process of linguistic substitution. The analysis of speakers’ subjectivity also shows that a relationship exists between linguistic insecurity and speakers’ knowledge of written Catalan, and, ultimately, a relationship between linguistic insecurity and speakers ’social mobility.